(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
Online gambling has become a prominent phenomenon among Bangkalan teenagers because it is considered a fast way to earn money instantly, and has even become the main source of income for some Bangkalan teenagers to meet their daily needs. However, serious attention to this phenomenon arises because it is considered detrimental to the future of Indonesia’s young generation, changing mindsets in earning a living and forming less productive personalities. Several cases involved Bangkalan teenagers who used money from their university fees to gamble without considering the risks, potentially threatening their ability to pay off education costs. Therefore, this research aims to identify the factors driving Bangkalan teenagers to engage in online gambling. Factors such as social, economic, situational, learning environment, perception of winning, and perception of addiction influence Bangkalan teenagers’ tendencies in online gambling, while secretive attitudes, difficulty accepting advice, stubbornness, and reluctance to admit or avoid potential dangers are obstacles. in dealing with this phenomenon.